1987
DOI: 10.1111/j.1526-4610.1987.hed2708439.x
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Inflammatory Meningeal Reaction Manifesting as a Migrainous Syndrome

Abstract: A female aged 24 years, without any previous personal and family history of migraine, presented with migrainous attacks characterized by headache, dizziness and nausea, accompanied by sensory, motor, visual and aphasic disturbances. The duration of the attacks ranged from 10-30 minutes, except for one episode which was accompanied by confusion and excitation and which lasted for many hours. The attacks recurred for approximately 6 weeks during which the condition of the patient was excellent between attacks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In some cases, the headache is described to be global, progressive and intense [6], other patients have pressure-like pain [7], sometimes the headache is constant and frontally localized [8] and others have a recurrent headache [9]. Single case reports show that headache in aseptic meningitis might be migraine-like [10][11][12] and even sufficiently treated with subcutaneous application of sumatriptan [10].…”
Section: Clinical Presentation Of Headache In Drug-induced Aseptic Mementioning
confidence: 98%
“…In some cases, the headache is described to be global, progressive and intense [6], other patients have pressure-like pain [7], sometimes the headache is constant and frontally localized [8] and others have a recurrent headache [9]. Single case reports show that headache in aseptic meningitis might be migraine-like [10][11][12] and even sufficiently treated with subcutaneous application of sumatriptan [10].…”
Section: Clinical Presentation Of Headache In Drug-induced Aseptic Mementioning
confidence: 98%
“…Of note, aseptic meningitis can cause migrainous headaches in patients like our subjects, who have a pre-existing diagnosis of migraine and, thus, carry a (genetic) predisposition to react to various stimuli with migraine attacks, but also in probands without a previous history of migraine [12,13]. In the latter group, however, using the operational diagnostic criteria of the IHS, the most appropriate diagnosis is headache attributed to lymphocytic meningitis (ICHD II 9.1.2), in particular, if the headache attacks completely subside after resolution of the viral infection.…”
mentioning
confidence: 98%
“…Cases of symptomatic migraine have been reported in various systemic and CNS disorders; in particular, migrainous headaches have been described in inflammatory/infectious conditions of the CNS, including aseptic [12,13] and bacterial [8,11] meningitis. Of note, a single case of herpes simplex virus type 1 infection causing migrainous headache has been reported [10].…”
mentioning
confidence: 98%
“…Our patient presented a series of migraine‐like headache attacks. Migraine‐like attacks associated with CSF abnormalities have been reported [3–7]. The ICHD‐II defines this condition as ‘syndrome of transient headache and neurological deficits with CSF lymphocytosis (HaNDL)’.…”
mentioning
confidence: 99%
“…Our patient presented a series of migraine-like headache attacks. Migraine-like attacks associated with CSF abnormalities have been reported [3][4][5][6][7]. The ICHD-II defines this condition as Ôsyndrome of transient headache and neurological deficits with CSF lymphocytosis (HaNDL)Õ. Gomez-Aranda et al [6] reported, in a series of 50 patients, that pain localization in HaNDL is more often bilateral, and that meningeal irritation signs are always absent.…”
mentioning
confidence: 99%